Is the Development of Offenders Related to Crime Scene Behaviors for Burglary? Including Situational Influences in Developmental and Life-Course Theories of Crime. (December 2016) - Fox, Bryanna Hahn; Farrington, David P.
Developmental and life-course (DLC) theories of crime aim to identify the causes and correlates of offending over the life span, focusing on the within-individual variations that result in criminal and delinquent behavior. Although there are several notable theories in the field, few contain both developmental and situational factors related to offending, and none explain why individuals commit crimes in different ways. This study aims to address these issues by developing typologies of burglars based on developmental and situational characteristics to help identify the various criminal career paths of the offenders, and how these different criminal careers may relate to the commission of offenses. Results of this study indicate that there are five different criminal career paths among the sampled burglars and four different styles of committing the same offense, and that burglars with certain criminal career features tend to commit a specific style of burglary. Through this research, we aim to extend DLC theories to create a more practical and contextual explanation of the relationship between criminal careers and the commission of offenses, and increase the level of within-individual explained variance in criminal behavior.